The Udder Side of Maritime Rights:: Bovine Tuberculosis and Federal Regulatory Power in 1920s Prince Edward Island - Jenkins, Jane (Acadiensis, 2011)
Abstract This article traces the federal program to eradicate bovine tuberculosis during the early 20th century, the dynamics of Prince Edward Island’s two-year battle to participate, and the motivation behind the unexpected decision to test PEI cows after steadfast refusals. Rather than a progress narrative, the article reveals the rise of the regulatory state in tandem with the authority of veterinary science – wielded in order to fracture the unity of regional dissent. The establishment of PEI as a zone free of bovine tuberculosis was thus as much about politics and profit as it was about public health and progressivism.